A program evaluation of an in-school daily physical activity initiative for children and youth - Emily Bremer; Jeffrey D. Graham; Scott Veldhuizen; John Cairney (BMC Public Health, 2018)
Abstract Background The school system is one setting in which children’s physical activity levels may be increased through daily physical activity (DPA) policies and initiatives. Adherence to DPA policies is typically poor and results are limited in regard to the associated benefits for participating children. Therefore, the purpose of this study was to evaluate a range of psychosocial outcomes following a community-led, in-school DPA initiative for 9–14 year old children and youth. Methods This program evaluation examined the impact of a DPA program consisting of 20 min of teacher-led DPA for 20 consecutive weeks. Student outcomes were measured using a questionnaire administered at three time points: baseline, mid-intervention, and post-intervention. A teacher questionnaire regarding program adherence and student behaviour was completed at post-intervention. Mixed effects models were used to test for intervention effects, with random intercepts for students, classes, and schools, as well as fixed effects for age and sex. Due to the large number of outcomes measured, we first conducted an omnibus test of the intervention effect followed by three exploratory analyses examining each outcome separately, associations between outcomes and program adherence, and results from the teacher survey. Results Thirty classes (N = 19 experimental) from 7 schools participated in the study, with a total of 362 children (n = 265 experimental). There was no significant overall effect of the intervention (z = 0.89, p = 0.38) and the exploratory analyses demonstrated significant differences only for self-esteem and subjective happiness, with the control group slightly increasing relative to the experimental group. Teacher-reported adherence to the program was poor with only 21% of teachers adhering to the program. There was no association between overall adherence and student reported outcomes; however, positive correlations were present between adherence and teacher-reported student behaviour. Conclusions The DPA program evaluated here did not improve the psychosocial well-being of elementary school-aged children more than usual practices. However, adherence to the program was poor and it did not have a negative effect on the students. Future work is needed on how best to support DPA implementation in the context of the school day and how student well-being may be positively impacted through school-based physical activity. Trial registration Program Evaluation of an in-school Daily Physical Activity Initiative NCT03618927, August 6, 2018. Retrospectively registered.